THE ROLES OF POLITICAL POWER IN BUDGET PROCESS: HOW TO ACCOMODATE THEM? A CASE STUDY - Zarista, Eden; Ichsan, Muhammad (Jurnal Tata Kelola & Akuntabilitas Keuangan Negara, 2020)
This research has two main objectives. The first objective is to identify the role of political power in the budgeting process, while the second is to propose a  control mechanism to enable a budgeting process to accommodate political power in terms of accountability. Indonesia?s Corruption Eradication Commission reports on the misuse of political power to manipulate budgeting in an organized manner. Execution of the budgeting process that does not follow the prevailing strategic policy constitutes fraud. The functions of budgeting are allocation, distribution, and stabilization. This study analyzes budgeting that intertwines with the wielding of political power. The study employed qualitative research supplemented by a case study to explain why and how such phenomena are occurring. The analysis was conducted using the thematic method by way of open-ended questionnaires to explain the data and information that were accumulated concerning the topic at hand and their relevance. Results show that political power plays both negative and positive roles. The positive aspect of the exercise of political power is that it is used as a public channel between society and the government, while its negative impact is the various risks that it poses, such as political power being used to advance self-interests. Political power does not share the same degree of impartiality as statutory rules. The form of politics can alter a budgeting activity or program. The application of a certain budgeting system is proposed to reduce errors and record activity history. Concerning the evaluation of APBD by the DPRD, APIP must help enforce control by reviewing budget changes against the relevant goals and objectives.